Intersectionality of Gender and Family Socio-Economic Status in the Trends of Moderate-to-Vigorous Physical Activity Among Baltic Adolescents (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To investigate moderate-to-vigorous physical activity (MVPA) trends among Baltic adolescents from 2001 to 2014, considering gender and socioeconomic indicators and their intersectionalities.Methods: Data from Estonia (2001, 2006, and 2014), Latvia (2001, 2006, and 2014), and Lithuania (2001 and 2006) were gathered from Health Behaviour in School-aged Children, comprising 36,426 adolescents (50.7% girls, mean age of 13.6 ± 1.6 years). Prevalences of self-reported MVPA were obtained using cut-offs (≤1 day/week and 7 days/week) and stratified considering the combination of gender (girl and boy) and family socio-economic status (low and high). Descriptive statistics were carried out through relative frequencies and their respective 95% confidence (95% CI), and absolute differences between groups were presented in percentage points (p.p.).Results: The prevalence of ≤1 day/week [2001: 11.5% (95% CI, 11.0–12.1); 2014: 9.9% (95% CI, 9.4–10.6)] and 7 days/week was stable throughout the analysed years [2001: 18.5% (95% CI, 17.8–19.1); 2014: 17.6% (95% CI, 16.9–18.4)]. Throughout the years, higher participation in MVPA was noticed among boys and adolescents with high socio-economic status. Intersectionalities revealed an absolute difference ~8.0 p.p. in prevalence of ≤1 day/week between girls with low socio-economic status [2001: 15.9% (95% CI, 14.9–17.0)] and boys with high socio-economic status [2001: 7.7% (95% CI, 6.6–8.9)], which was consistent throughout the analysed years [girls with lower socio-economic status, 2014: 14.1% (95% CI, 12.7–15.7); boys with higher socio-economic status, 2014: 6.6% (95% CI, 5.7–7.6)]. When 7 days/week was the outcome, an absolute difference of ~10 p.p. between girls with low socio-economic status [2001: 14.0% (95% CI, 13.0–15.0)] and boys with high socio-economic status [2001, 24.0% (95% CI, 22.2–25.8)] was observed throughout the years [girls with low socio-economic status, 2014: 12.4% (95% CI, 11.0–13.8); boys with  high socio-economic status, 2014: 23.8% (95% CI, 22.2–25.4)].Conclusion: Inequalities in MVPA are not limited to meeting international guidelines but are also evident when using more sensitive cut-offs. The intersectionality approach highlighted how gender and family socio-economic status influence engagement in MVPA, with no observed reduction in inequalities across the analysed outcomes. Future interventions should address the full spectrum of MVPA while considering the interplay of various power structures.